Konsep Integrasi Manajemen Bisnis Syariah Pondok Pesantren Melalui Bank Wakaf Mikro - Mahmudin, Mahmudin (DPPM Universitas Pelita Bangsa, 2024)
In the literature, micro waqf banks are predominantly associated with productive waqf literacy, women's economic empowerment, poverty alleviation, and providing business capital. However, the lack of literature on pesantren (Islamic boarding schools) managing sharia business with the presence of micro waqf banks motivated this research. This study highlights the importance of explaining the role of Sharia business management in pesantren that operate micro waqf banks. The research aims to understand sharia business management in pesantren integrated with micro waqf banks. A qualitative method with a literature study approach was used. The data, which is secondary, was sourced from books, journals, bulletins, proceedings, and reports from the last 12 years. The data analysis technique employed content analysis. The study found that the sharia business management of pesantren operating micro waqf banks involves planning, organizing, leading, and controlling to create and inventory sharia business potential sustainably according to the Qur'an and As-Sunnah. The integration of sharia business between pesantren and micro waqf banks involves the joint involvement of pesantren managers, micro waqf bank managers, and customers. The sharia business management of pesantren operating micro waqf banks can be conducted collaboratively among pesantren managers, micro waqf bank managers, and micro waqf bank customers. This research implies that the better the sharia business management of pesantren operating micro waqf banks, the more positive the socio-economic development will be for the pesantren and the surrounding community. Future research should analyze the impact of Sharia business management on strengthening the economy of pesantren operating micro waqf banks. The limitation of this study is the use of a literature study due to the limited literature on Sharia business management in pesantren based on micro waqf banks.